2019
DOI: 10.1039/c9cp00958b
|View full text |Cite
|
Sign up to set email alerts
|

High spin polarization in formamidinium transition metal iodides: first principles prediction of novel half-metals and spin gapless semiconductors

Abstract: The electronic structure shows that FAVI3 is a novel organic–inorganic hybrid perovskite-type spin gapless semiconductor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Fortunately, their multitude of crystallographic configurations, along with a wide palette of substituents, encouraged researchers to explore halide perovskites based on non‐toxic materials with enhanced performance 178 . The route to resolve the toxicity relies on Pb replacement with non‐toxic elements, 179 such as transition metals' divalent, trivalent or tetravalent cations 35,127,178,180 via experience‐driven short‐listing and trial‐and‐error methodologies 178 …”
Section: Electronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, their multitude of crystallographic configurations, along with a wide palette of substituents, encouraged researchers to explore halide perovskites based on non‐toxic materials with enhanced performance 178 . The route to resolve the toxicity relies on Pb replacement with non‐toxic elements, 179 such as transition metals' divalent, trivalent or tetravalent cations 35,127,178,180 via experience‐driven short‐listing and trial‐and‐error methodologies 178 …”
Section: Electronic Propertiesmentioning
confidence: 99%
“…It is worth noting that extra PbI 2 forming from the combination of the released Pb 2+ ions with I − ions improves the stability and the PCE 126 . Besides, replacing different transition metal TM atoms with Pb is investigated theoretically by Huang et al 127 They observed an enhancement in tolerance factor and consequent stabilization of the cubic phase because of using these transition metal atoms.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…In this regard, ferromagnetic (FM) half-metals, which are in a metallic state in one spin channel while in a semiconducting or insulating state in other spin channels, provide completely spin-polarized electrons around the Fermi level and are thereby an ideal source of spin injection. [1][2][3] Indeed, the discovery of FM half-metals opens the way for numerous applications including spin filters, spin diodes, spin valves, spin field effect transistors and spin Seebeck devices. [4][5][6][7][8] In recent years, two-dimensional (2D) FM materials as promising candidates for nanoscale spin-based devices have become a central topic of spintronics research.…”
Section: Introductionmentioning
confidence: 99%
“… Wang, (2008) proposed that by introducing magnetic ions into the parent nonmagnetic gapless compounds, such as PbPdO 2 , the spin-gapless semiconducting state can appear. Based on his work, a series of spin-gapless semiconductors ( Li et al, 2009 ; Gao et al, 2015 ; Wang et al, 2016a ; Galanakis et al, 2016 ; Gao et al, 2016 ; He et al, 2017 ; Wang, 2017 ; Deng et al, 2018a ; Huang et al, 2019a ; Nadeem et al, 2020 ; Yue et al, 2020 ; Yang et al, 2021 ) with parabolic or linear dispersion between energy and momentum are proposed. More interestingly, topological signatures, such as Dirac point and nodal line states, can be found in spin-gapless semiconductors.…”
Section: Introductionmentioning
confidence: 99%